Pengembangan Potensi Konsentrat Buah Pare (Momordica charantia L.) sebagai Pencegahan Hiperkolesterol pada Mencit Jantan (Mus musculus) - Farah Sulistyaningtyas; Zestyla Oktraiani (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2024)
Background: Hypercholesterolemia is a condition characterized by an increase in cholesterol levels in the blood above the normal limit. Parsley contains some phytochemicals such as niacin, vitamin C, vitamin E, flavonoids, and saponins that are believed to lower blood cholesterol levels. This study aimed to determine the anti-cholesterolemia activity and dose concentration of ethanol concentrate steam in male rat scratches to prevent hypercholesterolemia. Pre-test and post-test research design using random sampling techniques. Animal trials used used twenty-five pairs of scissors, divided into five groups. One control group was given a standard diet and 0.2 ml NaCMC suspension, and four treatment groups were given additional oral treatment with standard diets and a dose of 0.02 ml suspension. Simvastatin, an ethanol concentrate of pear fruit, is given in doses of 0.5 ml/day, 1 ml/day, and 1.5 ml/day for 7 days—total cholesterol analysis using a cholesterol strip. The data obtained were analyzed using the ANOVA one-way test in SPSS 23. The administration of simvastatin and ethanol concentrate in the treatment group decreased total cholesterol levels compared to controls at all doses. The third dose concentration was ethanol concentrate of the fruit, with a dose of 1.5 ml/day, because it lowered the overall cholesterol level compared with the control group, treatment 2, and treatment 3. Based on the table of the one-directional ANOVA test, the results were achieved when the probability value (p) = 0,000 or the value (P) < 0,05. The resulting conclusion was that there was an average significant difference between normal cholesterol, high fat, and post-treatment. Keywords:  Cholesterol, Hypercholesterolemia, Simvastatin, Ethanol concentrate of bitter melon (Momordica charantia L)